The Long-term Effects of Uncultured Omental Adipose-derived Nucleated Cells Fraction and Bone-marrow Stromal Cells on Sciatic Nerve Regeneration - Saeed Azizi; Behnam Heshmatian; Saman Mahmoudpour; Abbas Raisi (Iranian Journal of Veterinary Surgery, 2015)
Objective- Adipose tissue is an appropriate source for isolation of cells with stem-cell-like properties. In the present long-term study, the effects of the omental adipose-derived nucleated cells (OADNCs) fraction were compared to those of the undifferentiated cultured bone marrow stromal cells (BMSCs) on sciatic nerve regeneration. Design- Experimental in vivo study. Animals- Fifty male White Albino rats. Procedures- The rats were divided into four experimental groups, randomly: Normal control (NC), inside-out vein graft (IOVG), the OADNC and the BMSC groups. A 10-mm sciatic nerve defect was bridged using an inside-out vein graft. In OADNC and BMSC groups, the vein was filled with OADNCs and BMSCs, respectively. Functional studies of sciatic function index, electrophysiologic, morphometric and immunohistochemistry assessments were performed at 16, 20 and 24 weeks after surgery. Results- There was no significant differences (P > 0.05) between BMSC and OADNC groups concerning recovery of the regenerated nerves, amplitude and time delay of electromyography. Compared to IOVG, OADNCs enhanced the nerve regeneration similar to undifferentiated BMSCs. Conclusion and Clinical Relevance- It was concluded the long-term morphometric results could be more reliable in histological study of sciatic nerve regeneration.